2014
DOI: 10.1016/j.bbrc.2014.03.133
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin coating of TiO2 scaffold induces osteogenic differentiation of human adipose tissue-derived mesenchymal stem cells

Abstract: Bone tissue engineering requires an osteoconductive scaffold, multipotent cells with regenerative capacity and bioactive molecules. In this study we investigated the osteogenic differentiation of human adipose tissue-derived mesenchymal stem cells (hAD-MSCs) on titanium dioxide (TiO2) scaffold coated with alginate hydrogel containing various concentrations of simvastatin (SIM). The mRNA expression of osteoblast-related genes such as collagen type I alpha 1 (COL1A1), alkaline phosphatase (ALPL), osteopontin (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…This result may have arisen from the relatively early time points we chose for detection, during which OCN expression is at a relatively low level and less sensitive to simvastatin stimulation. A previous in vitro study reported that simvastatin‐treated adipose tissue‐derived mesenchymal stem cells showed significant elevated expression of ALP and COL1, but not OCN, at 7 and 14 days . Moreover, another study reported similar results to our present finding, as periodontal ligament cells showed significant calcium accumulation at 21 days, but not 7 or 14 days after simvastatin stimulation .…”
Section: Discussionsupporting
confidence: 90%
“…This result may have arisen from the relatively early time points we chose for detection, during which OCN expression is at a relatively low level and less sensitive to simvastatin stimulation. A previous in vitro study reported that simvastatin‐treated adipose tissue‐derived mesenchymal stem cells showed significant elevated expression of ALP and COL1, but not OCN, at 7 and 14 days . Moreover, another study reported similar results to our present finding, as periodontal ligament cells showed significant calcium accumulation at 21 days, but not 7 or 14 days after simvastatin stimulation .…”
Section: Discussionsupporting
confidence: 90%
“…This finding was corroborated by the other tests performed in this study, which evaluated levels of apoptosis of HDPCs and HPLFs by flow cytometry after Annexin V/propidium iodide double staining, actin cytoskeleton and nuclear morphology by phalloidin-FITC and 40,6-diamidino-2-phenylindole dihydrochloride staining, in which no cell structure damage was observed under these conditions. 29 Moreover, some researchers have demonstrated a decrease in cell viability mediated by SV for other types of cells, such as smooth muscle cells, 31 neuronal cells, 32 bone marrow stem cells (BMSC), 33 adipose derivate mesenchymal stem cells (AD-MSC) 34 and hDSPCs cells. 22 Okamoto et al 14 reported that when SV concentrations higher than 1 µM were applied to hDSPCs cells, they inhibited the formation of actin fibers and interfered with progression of the cell cycle regulated by the Rho pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another equally attractive synthetic drug currently utilized in bone tissue engineering which is able to mimic the effect of BMP-2 is simvastatin which has been shown to enhance bone formation in particular by promoting the differentiation of cells into the osteogenic lineage. This has been reported in a study by Pullisaar et al [14] where osteogenic differentiation was achieved in human adipose tissuederived mesenchymal stem cells due to the presence of simvastatin.…”
Section: Commonly Employed Drugs In Bone Tissue Engineeringmentioning
confidence: 56%